1981
DOI: 10.1109/edl.1981.25319
|View full text |Cite
|
Sign up to set email alerts
|

A new edge-defined approach for submicrometer MOSFET fabrication

Abstract: A novel technique emploging vertical (anisotropic) dry etching for fabricating edge-defined submicrometer MOSFETs is described, and preliminary results are presented. Three basic process techniques are employed: formation of En edge-defined submicrometer element, pattern transfer of the element into an underlying doped polysilicon gate layer, and passivation of the FET using a sidewall oxide. The submicrometer element formation technique is limited to linewidths in the 0.1 pm to 0.4 pm range. Characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Processes such as sidewall transfer lithography (STL) allow parallel fabrication of restricted feature sets. This method combines repeated STL (originally developed for field-effect transistor fabrication [3,4] and subsequently used for other features such as nanowires [5]) with standard MEMS processing [6,7] to form more general structures [8,9]. However, the need for metrology remains.…”
Section: Introductionmentioning
confidence: 99%
“…Processes such as sidewall transfer lithography (STL) allow parallel fabrication of restricted feature sets. This method combines repeated STL (originally developed for field-effect transistor fabrication [3,4] and subsequently used for other features such as nanowires [5]) with standard MEMS processing [6,7] to form more general structures [8,9]. However, the need for metrology remains.…”
Section: Introductionmentioning
confidence: 99%
“…The main characteristic of SAMP processes is the consecutive sidewall-spacer steps that enable spatial frequency multiplication. The fabrication technique to use spacers to pattern dense and fine features (e.g., transistor gates [33][34][35] and MEMS/NEMS devices [36][37][38]) dates back to several decades ago. As a density multiplication concept, it had been well known in our IC lithography/processing society for a long time despite some misunderstanding that it was invented just recently.…”
Section: Introductionmentioning
confidence: 99%
“…In each case the cost and complexity of the patterning step may prevent the translation of NEMS into practical use. Recently, a fabrication process based on sidewall transfer lithography [5][6][7][8][9][10][11] has been demonstrated that allows ultrathin suspensions to be combined with microscale anchors and hence form NEMS such as the electrothermal actuator in Fig. 1 [12].…”
Section: Introductionmentioning
confidence: 99%